Application Of Transportation Method In Optimizing The Cost Of Equal Distribution Of Zakat Fitrah In Ngaglik District, Sleman, Yogyakarta - Ilham Achmad Fiqrin; Dina Thaib; Taufiq Hidayat (International Journal of Health Engineering and Technology, 2026)
Zakat is a form of worship that can bring many benefits to Muslims, especially zakat fitrah. However, several problems remain frequently encountered in the implementation of zakat fitrah, one of which is the distribution of varying amounts of rice in each region. To address this issue, it is necessary to equalize the distribution of zakat fitrah. This can be achieved by distributing zakat fitrah to regions receiving more rice, especially those receiving less. To achieve this, it is necessary to find an effective method to make the distribution process more efficient. One method that can be used is transportation, which will make the allocation of goods more effective in terms of labor, time, and costs. In the case of zakat fitrah, each region acts as both a source and a destination. The source supply is based on the amount of zakat fitrah received, while the destination demand is based on the number of zakat recipients in each region. This study uses data from hamlets in Ngaglik sub-district, Sleman, Yogyakarta. The solution to the equitable distribution of zakat fitrah is solved using a transportation model with the North-West Center method, the Least Cost method, and the Vogel Approach Method (VAM) which is useful for analyzing initial feasibility. The minimum solution of the three methods is obtained by the Least Cost Method; Modified Distribution (MODI) to analyze the optimum solution. From the calculation of the transportation method, the optimum cost is obtained at Rp. 972,350.00; zakat fitrah recipients receive the same amount of 5.6 kg per head of family; and the determination of zakat fitrah delivery from one region to another.